ACST-2-an update. A large, simple randomised trial to compare carotid endarterectomy versus carotid artery stenting to prevent stroke in asymptomatic patients - Bulbulia, R; Halliday, A (Springer, 2013)
Introduction ACST-2 is a large and simple stream-lined trial which aims to compare both the early hazards and long-term durability of carotid endarterectomy (CEA) versus carotid artery stenting (CAS) in asymptomatic  patients with high-grade carotid artery stenosis. Methods Patients are eligible for ACST-2 if they have a severe carotid artery stenosis and intervention is clearly indicated, with both CEA and  CAS practicable, but where there is substantial uncertainty as to which intervention is best. Collaborating  surgeons and stenters may use their usual techniques and any CE-marked devices are permitted. Results ACST-2 aims to recruit several thousand patients by 2019. To date, over 1200 patients have been randomised by  study collaborators working in 79 centres across 25 countries. Italy is the top recruiting country, followed by  the UK and Sweden. Interim blinded analyses reveal a 1% rate of serious 30-day postprocedure complications (disabling stroke, myocardial infarction or death). Discussion ACST-2 is the only trial designed to reliably compare the short-term hazards and long-term benefits of CEA versus CAS in asymptomatic patients, and it complements other carotid  trials which compare intervention versus medical management (e.g. SPACE-2). If, as seems likely, these trials show benefit from carotid intervention in addition to  contemporary medical management in selected patients, then whether to perform CEA or CAS  will remain a highly relevant question, and one only ACST-2 can answer.